2006
DOI: 10.1109/tgrs.2006.870234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foam on ocean surface microwave emission inferred from radiometric observations of reproducible breaking waves

Abstract: Abstract-WindSat, the first satellite polarimetric microwave radiometer, and the NPOESS Conical Microwave Imager/Sounder both have as a key objective the retrieval of the ocean surface wind vector from radiometric brightness temperatures. Available observations and models to date show that the wind direction signal is only 1-3 K peak-to-peak at 19 and 37 GHz, much smaller than the wind speed signal. In order to obtain sufficient accuracy for reliable wind direction retrieval, uncertainties in geophysical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…At microwave frequencies, the sea foam has higher surface emissivity than water (Wentz, 1997;Rose et al, 2002) and affects microwave radiometric retrievals of ocean-surface wind vector (Yueh, Wilson, Dinardo, & Li, 1999;Padmanabhan, Reising, Asher, Rose, & Gaiser, 2006) and salinity (Camps et al, 2005).…”
Section: Foam Emissivity From Incoherent Approachmentioning
confidence: 99%
“…At microwave frequencies, the sea foam has higher surface emissivity than water (Wentz, 1997;Rose et al, 2002) and affects microwave radiometric retrievals of ocean-surface wind vector (Yueh, Wilson, Dinardo, & Li, 1999;Padmanabhan, Reising, Asher, Rose, & Gaiser, 2006) and salinity (Camps et al, 2005).…”
Section: Foam Emissivity From Incoherent Approachmentioning
confidence: 99%
“…As an example, at 10.8 GHz and 36.5 GHz, Rose et al [8] obtained a formula of foam emissivity by means of a power-series polynomial of incidence angles for foam thickness 2.8 cm. To investigate effects of breaking waves and the foam layer on sea surface brightness temperatures, Padmanabhan et al [24] conducted an emissivity experiment of the wave-breaking surface at 10.8, 18.7, and 37 GHz. With experiments on various foam shapes and foam-water interfaces, Williams [25] showed that the meniscus of the foam-water interface can contribute a significant fraction of foam emissivity increments at 9.2 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…1453 in [36] λ 0 free-space wavelength (6) Propagation constant (wave number) [37] Scattering parameters (7) Size parameter x [37] a bubble radius…”
Section: Equation #mentioning
confidence: 99%
“…Vertical variations of the real part of the permittivity in foam thickness invoke changes in the radiation wavelength λ f and propagation constant k f as compared to that in air λ 0 (Equations (5) and (6) in Table 1). Table 2 shows values of λ f in dry and wet foam represented with f a = 98% and 10%, respectively, for all considered frequencies.…”
Section: Wavelength Changes In Foam Layersmentioning
confidence: 99%
See 1 more Smart Citation